Observation of B+c → J/ψD+s and B+c → J/ψD*+s decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
The decays B+c→J/ψD+s and B+c→J/ψD*+s are observed for the first time using a dataset, corresponding to an integrated luminosity of 3 fb−1, collected by the LHCb experiment in proton-proton collisions at center-of-mass energies of √s=7 and 8 TeV. The statistical significance for both signals is in excess of 9 standard deviations. The following ratios of branching fractions are measured to be B(B+c→J/ψD+s)B(B+c→J/ψπ+)=2.90±0.57±0.24, B(B+c→J/ψD*+s)B(B+c→J/ψD+s)=2.37±0.56±0.10, where the first uncertainties are statistical and the second systematic. The mass of the B+c meson is measured to be mB+c=6276.28±1.44(stat)±0.36(syst) MeV/c2, using the B+c→J/ψD+s decay mode.